2015
DOI: 10.1155/2015/240948
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Surfactant on the Growth and Oxidation of Iron Nanoparticles

Abstract: Fe nanoparticles and branched nanostructures of iron oxide were synthesized by chemical reduction in aqueous phase. The mechanism of formation of iron oxides as a function of the amount of surfactant employed during the synthesis process was studied. Specifically Fe, Fe2O3, and Fe3O4nanoparticles were obtained. The oxidation of Fe to Fe3O4and finally to Fe2O3was carried out by oxidative etching process, decreasing the amount of stabilizer agent. The structures obtained were characterized by high resolution (HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(61 citation statements)
references
References 28 publications
4
54
0
3
Order By: Relevance
“…Moreover, the SEM images of MB materials pyrolyzed at diferent temperatures were shown in figure S5. Figure 4(a) [34,35]. In figure 4(b), all these peaks appear again in the XRD spectrum of MB500 and some peaks of the MB500 shifted such as 30.05 o , 43.48 o , and 56.50 o .…”
Section: Characterization Of Biocharmentioning
confidence: 82%
See 2 more Smart Citations
“…Moreover, the SEM images of MB materials pyrolyzed at diferent temperatures were shown in figure S5. Figure 4(a) [34,35]. In figure 4(b), all these peaks appear again in the XRD spectrum of MB500 and some peaks of the MB500 shifted such as 30.05 o , 43.48 o , and 56.50 o .…”
Section: Characterization Of Biocharmentioning
confidence: 82%
“…In figure 4(b), all these peaks appear again in the XRD spectrum of MB500 and some peaks of the MB500 shifted such as 30.05 o , 43.48 o , and 56.50 o . The major peak at 35.83 of MB500 is correlated with the peak at 35.05 o of standard which is for a crystalline plane with Miller indices of (311) [9,35]. Therefore, the iron oxide precipitation by thermal process, Fe 3 O 4 is formed.…”
Section: Characterization Of Biocharmentioning
confidence: 92%
See 1 more Smart Citation
“…IR spectra of the synthesized PVA-Fe3O4 and PVA-GA-Fe3O4 nanoparticles showed -OH (3394 -3386 cm , as similar result was also reported by Ruíz-Baltazar. 27 This information indicated that the hydroxyl groups were successfully replaced by PVA and PVA-GA, so the oxidation of Fe3O4 could be prevented. XRD patterns proved the existence of magnetite (Fe3O4) and maghemite (γ-Fe2O3) phases in all prepared materials while PVA phases could be identified in PVA-Fe3O4 and PVA-GA-Fe3O4 materials as shown in Fig.-3.…”
Section: Ftir and Xrd Patterns Of Pva-coated Fe3o4 Nanoparticlesmentioning
confidence: 96%
“…The reaction mixture changed from light yellow to colorless. The catalytic reaction using Au@PNIPAm/PEI (amine to gold molar ratio of 28:1) and Ag@Au/PNIPAm/PEI [amine to gold and silver ions ratio (N/Au 3+ Ag + ) of 28:1] were systematically studied under different solution pH values (3)(4)(5)(6)(7)(8)(9)(10)(11) and temperatures (25-39˝C). The reduction of p-nitrophenol to p-aminophenol was monitored by the UV-visible spectroscopy (Agilent Technologies, Santa Clara, CA, USA) at a wavelength of 400 nm for 20 min.…”
Section: Catalytic Activity Of Nanocomposite Particlesmentioning
confidence: 99%